Natural dualities for varieties generated by a set of subalgebras of a semi-primal algebra - Mathonet, P.; Niederkorn, P.; Teheux, B. (Algebra and Discrete Mathematics, 2007)
The main contribution of this paper is the construction of a strong duality for the varieties generated by a set of
subalgebras of a semi-primal algebra. We also obtain an axiomatization of the objects of the dual category and develop some algebraic consequences (description of the dual of the finite structures
and algebras, construction of finitely generated free algebras,. . . ).
Eventually, we illustrate this work for the finitely generated varieties of MV-algebras.